Redesain Kompor Briket Berbasis Sistem Kontrol Menggunakan Kansei Engineering - Saufik Luthfianto; Siswiyanti Siswiyanti; Inayatu Amanah (Program Studi Teknik Industri Universitas Setia Budi, 2020)
Briquette stove is designed using the Kansei Engineering method. Beginning with interviews with respondents to produce interpretations of needs, then the interpretation of needs is summarized into several words kansei that are relevant to the design of briquette stoves, then the word kansei is tested with the first questionnaire test after that followed by questionnaire 2 about the specifications of the stove. The purpose of this research is to design a briquette stove based on a control system and increase the elasticity of the fabric and the adhesive at night using engineering kensei. The results of the redesign of the briquette stove based on the control system using Kansei Engineering are portable briquette stoves using an arduino-based temperature sensor and the adhesive power test results in a batik night adhesion level rising by 33.3% while for the elasticity test the batik night that is heated with a new stove produces more cracks small is up by 100%.